2014
DOI: 10.1007/s13197-014-1298-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the functional properties of three legume seed isolates: adzuki, pea and soy bean

Abstract: The aim of this work was to compare functional properties including solubility, emulsifying and foaming properties of native and thermally treated adzuki, soy and pea protein isolates prepared under the same conditions. These functional properties were tested at four pH values: pH 3.0, pH 5.0, pH 7.0 and pH 8.0. The lowest solubility at all pH values were obtained for isolate of adzuki whereas isolates of soybean had the highest values at almost all pHs. Thermal treatment reduced solubility of soy and pea isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 43 publications
7
58
0
1
Order By: Relevance
“…Figure 2 shows the percent of protein solubility depending on the pH samples (legume flours) studied. All the native flours studied showed a similar behaviour exhibiting the lowest value of solubility at pH 4 (10-13%), which is in coincidence with the isoelectric point of the proteins present in the samples tested (Barac et al, 2015). In contrast, higher solubility values were observed at alkaline pH (70-95%), and PP flour exhibited the highest values.…”
Section: Scanning Electron Microscopysupporting
confidence: 63%
See 1 more Smart Citation
“…Figure 2 shows the percent of protein solubility depending on the pH samples (legume flours) studied. All the native flours studied showed a similar behaviour exhibiting the lowest value of solubility at pH 4 (10-13%), which is in coincidence with the isoelectric point of the proteins present in the samples tested (Barac et al, 2015). In contrast, higher solubility values were observed at alkaline pH (70-95%), and PP flour exhibited the highest values.…”
Section: Scanning Electron Microscopysupporting
confidence: 63%
“…1e and f). All the native flours studied showed a similar behaviour exhibiting the lowest value of solubility at pH 4 (10-13%), which is in coincidence with the isoelectric point of the proteins present in the samples tested (Barac et al, 2015). Figure 2 shows the percent of protein solubility depending on the pH samples (legume flours) studied.…”
Section: Scanning Electron Microscopysupporting
confidence: 60%
“…Decreases in EAI and ESI of protein isolates from processed chickpea seeds might be balanced by the increased surface hydrophobicity and the decreased solubility of proteins (Yu et al ., ). The isolates from raw and soaked chickpea seeds have a higher EAI values than those from non‐treated adzuki, pea and soybean, while EAI values of thermally treated samples are comparable to their counterparts in previous studies (Zhang et al ., ; Barac et al ., ). However, our ESI results are lower than previously published values of 20.3–26.7 min in Kabuli chickpea protein isolates (Withana‐Gamage et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…This agrees with Barac et al . () who reported that thermal treatment reduced solubility of soy and pea isolates at all pH values. Decreased PS following thermal processing could be attributed to (i) protein denaturation and polymerisation by the disulphide bond interchange reaction, (ii) altered exposure of hydrophobic groups and (iii) aggregation of unfolded protein molecules into lower stable energy configurations (Avanza et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Also, the paper deals with the possible use of limited enzymatic hydrolysis as a method for the improvement of their techno-functional properties.2 tein isolates, whereas some other (5,13,14) pointed out better properties of pea isolates. Variations in the results among different studies could be due to the differences in the protein purity of the studied samples, method of protein isolation, the specific conditions used for the tests, as well as the different processing conditions (7,15). Furthermore, significantly different functionalities among pea isolates were observed.…”
mentioning
confidence: 99%